Análise do perfil clinico e epidemiologico de pacientes com diversos tipos de canceres, na região sudeste, no período pre pandemia e de pandemia de covid 19: Um estudo retrospectivo - Teixeira, Anna Carolina Faria Sassioto (2023)
Cancer ranks second on the list of leading causes of death in Brazil, trailing only behind heart diseases. Among the most prevalent types of malignant cancers are non-melanoma skin cancer (31.3%), female breast cancer (10.5%), prostate cancer (10.2%), colon and rectal cancer (6.5%), lung cancer (4.6%), and stomach cancer (3.1%). The COVID-19 pandemic marked a historical period that divided the world into three distinct phases: pre-pandemic, pandemic, and post-pandemic. The aim of this study was to analyze the epidemiological profile, diagnostic stage, temporal trends, and comparisons between the pre-pandemic period (2017 to 2019) and the pandemic period (2020 to 2022) in the Southeast region. The SUS oncology database was used through TABWIN. From this data, the incidence rate (per 100 inhabitants) and other statistics were calculated. To calculate the temporal trend of cancer incidence rates, segmented regression was employed. To compare the mean time between diagnosis and treatment during the pre-pandemic and pandemic periods, Welch's t-test with Cohen's effect size was used to assess the magnitude of differences. To examine significant differences in the staging grades of each cancer type between the pre-pandemic and pandemic periods, as well as the amount of missing or unreported data between these periods, the Chi-square test with Kramer's V as a measure of effect size was used for the entire Southeast region. The significance level for this study was set at p < 0.05. In conclusion, the analysis of the temporal trends in cancer incidence rates revealed that in Espírito Santo, stomach and non-melanoma skin cancers showed an increasing trend, while in São Paulo, only stomach cancer exhibited a similar trend. Men had a higher incidence than women in stomach, rectal, and lung cancers, with a moderate impact. Regarding staging, it was observed that during the pandemic period, there was a significant increase in stage IV incidence, while during the pre-pandemic period, stages 0 and I were more frequent, with medium and small effects, respectively. Data loss during the pre-pandemic period amounted to 11.46% of the data (54,080 cases), while during the pandemic, it reached 27.52% (129,869 cases), a statistically significant and substantial difference.